Early storybook reading and childhood development: A cross-sectional study in Iran [version 1; referees: 2 approved] - Firoozeh Sajedi; Elham Habibi; Nikta Hatamizadeh; Soheila Shahshahanipour; Hosein Malek Afzali (F1000Research, 2018)
Background: Development is a process that continues from childhood to death, and most developmental changes occur during childhood. UNICEF introduced early storybook-reading (ESR) and storytelling as part of child care indicators. The aim of this study was to investigate the status of book-reading to children and its relationship with early childhood development in Iran. Methods: This is a descriptive-analytic study conducted in Tehran April-May 2017. In total, 272 mothers of children aged 3-30 months, who were referred to health centers, were selected using a convenience sampling method. Exclusion criteria was scoring below the cutoff point of any developmental domains of the Ages and Stages Questionnaire (ASQ). ESR was assessed by checklist and child development was assessed by the ASQ. Data were analyzed using SPSS. Results: The mean number of children’s books owned was 10.23±8.642, and 84.75% had at least 3 books. The average book reading, storytelling and singing duration for children was 10±9.65, 11.48±11.756, and 23.88 ±17.880 min per day, respectively. Average book reading, storytelling, and singing duration was significantly greater in children 18-30 months than <17 months. There was a significant relationship between the number of books and a child's age, mother's age, family income, income satisfaction, father's employment, and parents’ education. The score of communication domain in the ASQ questionnaire was significantly related to the number of books, duration of reading and storytelling, while problem-solving had a significant relationship only with the number of books (p˂0.05). Based on linear regression, child's age, income, and mother's and father's educational level were models for predicting the number of children's books (p=0.0001 for all). Conclusions: ESR was associated with some developmental domains of communication and problem-solving in the present study. Therefore, creation of ESR culture in Iranian families as an integral part of the life of children is necessary from birth.